Effectiveness of different persuasive appeals on consumers - Ang, Candace Li Ling (2008)
This study investigates the effectiveness of using different persuasive appeals in a lipstick print ad. The different kinds of persuasive appeals studied include rational appeal, emotional appeal and a combination of both appeals. The effectiveness of the appeals depends on a variety of product- and reader-related factors. A review of past researches showed that products such as lipstick are more effectively advertised using emotional appeals. However, this study found that a combination of rational and emotional appeals was more effective than when the appeals were used in isolation. The effectiveness of the appeals was measured using consumer’s attitude toward the lipstick and their purchase intention. In this study, we found that when consumers have a positive attitude toward the advertisement, purchase intention will also be high. In addition, we realized women value both the functional and emotional benefits of a lipstick. We also considered the implications of this study to advertisers of lipstick. With the saturation of advertisements in everyday life, it is important for advertisers to break through advertising clutter to appeal effectively to their target consumers. It appears that the existing method adopted by advertisers of using a combination of appeals is the most appealing to consumers.